Color masking prediction of posterior white spot lesions by resin infiltration in vitro - de Oliveira Correia, Ayla Macyelle [UNESP]; Bühler Borges, Alessandra [UNESP]; Torres, Carlos Rocha Gomes [UNESP] (Elsevier, 2020)
Objective: To investigate parameters that could predict the color masking effect (ME) of white spot lesions (WSLs) after resin infiltration (RI). Methods: Sixty extracted human teeth with natural WSLs were selected (28 premolars, 29 molars and 3 incisors). At baseline, the laser fluorescence (LF) of surrounding sound enamel (SE) and the WSLs were analyzed with DIAGNOdent. Standardized photographs were obtained under D65 and UV illuminants, from which the CIE L*a*b* color coordinates and natural fluorescence (NF) of the WSLs and SE were obtained. The color difference (ΔE00) and differences of NF and LF between the SE and WSLs were calculated. The lesion dimensions (area, perimeter, width, and height) were determined. After RI, the assessments were repeated. ME was considered as the reduction of ΔE00 values after RI. One-way ANOVA and the Tukey tests were used to analyze the absolute means of the LF and NF values. The t test was used to compare the ΔE00 values and lesion dimensions before and after infiltration. The correlations between all parameters at baseline and ME were analyzed. Results: The absolute mean values of LF at the baseline (B) and after infiltration (I) were SE/B-3.98a, WSL/B-13.28c, SE/I-3.36a, WSL/I-7.95b (p = 0.001). The mean values for NF were SE/B-7.93a; WSL/B-6.29b, SE/I-7.93a, WSL/I-7.27a (p = 0.001). The results for ΔE00 were B-11.74a, I-8.66b (p = 0.001). RI significantly reduced lesion dimensions. No correlations were observed between the baseline parameters and the ME. Conclusions: The WSLs presented higher LF and smaller NF than SE, which were respectively reduced and increased after RI. Prediction of the masking effect by the parameters evaluated at baseline was not possible, which could be due to the choice of mainly caries lesions in posterior teeth. Nonetheless, infiltration was found suitable to mask most of the WSL. Clinical significance: The color masking effect of white spot lesions after resin infiltration cannot be predicted by a previous analysis of fluorescence, color, or dimensions of the lesion.
Keywords: Color; Dental caries; Fluorescence; Resin infiltration; White spot lesion